Favorable Trisomies and ETV6-RUNX1 Predict Cure in Low-Risk B-Cell Acute Lymphoblastic Leukemia: Results From Children's Oncology Group Trial AALL0331. Issue 14 (10th May 2021) - Mattano, Leonard A.; Devidas, Meenakshi; Maloney, Kelly W.; Wang, Cindy; Friedmann, Alison M.; Buckley, Patrick; Borowitz, Michael J.; Carroll, Andrew J.; Gastier-Foster, Julie M.; Heerema, Nyla A.; Kadan-Lottick, Nina S.; Matloub, Yousif H.; et al.
Abstract : PURPOSE: Children's Oncology Group (COG) AALL0331 tested whether pegaspargase intensification on a low-intensity chemotherapy backbone would improve the continuous complete remission (CCR) rate in a low-risk subset of children with standard-risk B-acute lymphoblastic leukemia (ALL). METHODS: AALL0331 enrolled 5, 377 patients with National Cancer Institute standard-risk B-ALL (age 1-9 years, WBC < 50, 000/μL) between 2005 and 2010. Following a common three-drug induction, a cohort of 1, 857 eligible patients participated in the low-risk ALL random assignment. Low-risk criteria included no extramedullary disease, < 5% marrow blasts by day 15, end-induction marrow minimal residual disease < 0.1%, and favorable cytogenetics ( ETV6-RUNX1 fusion or simultaneous trisomies of chromosomes 4, 10, and 17). Random assignment was to standard COG low-intensity therapy (including two pegaspargase doses, one each during induction and delayed intensification) with or without four additional pegaspargase doses at 3-week intervals during consolidation and interim maintenance. The study was powered to detect a 4% improvement in 6-year CCR rate from 92% to 96%. RESULTS: The 6-year CCR and overall survival (OS) rates for the entire low-risk cohort were 94.7% ± 0.6% and 98.7% ± 0.3%, respectively. The CCR rates were similar between arms (intensified pegaspargase 95.3% ± 0.8% v standard 94.0% ± 0.8%; P = .13) with no difference in OS (98.1% ± 0.5% v 99.2% ± 0.3%; P = .99). Compared to a subset of standard-risk study patients given identical therapy who had the same early response characteristics but did not have favorable or unfavorable cytogenetics, outcomes were significantly superior for low-risk patients (CCR hazard ratio 1.95; P = .0004; OS hazard ratio 5.42; P < .0001). CONCLUSION: Standard COG therapy without intensified pegaspargase, which can easily be given as an outpatient with limited toxicity, cures nearly all children with B-ALL identified as low-risk by clinical, early response, and favorable cytogenetic criteria.